2012
DOI: 10.1021/om3006239
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Palladium Complexes with a Water-Soluble Iminophosphorane Ligand As Potential Anticancer Agents

Abstract: The synthesis and characterization of a new water-soluble iminophosphorane ligand TPAN-C(O)-2BrC6H4 (1, C,N-IM; TPA = 1,3,5-triaza-7-phosphaadamantane) is reported. Oxidative addition of 1 to Pd2(dba)3 affords the orthopalladated dimer [Pd(μ-Br){C6H4(C(O)NTPA-kC,N)-2}]2 (2) as a mixture of cis and trans isomers (1:1 molar ratio) where the iminophosphorane moeity behaves as a C,N-pincer ligand. By addition of different neutral or monoanionic ligands to 2, the bridging chlorides can be cleaved and a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 92 publications
(131 reference statements)
11
55
0
Order By: Relevance
“…It may indicate that the substitution of ligands affects the binding of complexes with BSA. A similar effect (more than one binding site) was observed in the interaction of cyclometallated iminophosphorane complexes and HSA as well [6]. Moreover this same effect was observed in a quantitative way (by isothermal calorimetry ITC) with other coordination palladium iminophosphorane complexes [35].…”
Section: Fluorescence Quenching Of Bsa By Complexes 1e8supporting
confidence: 69%
“…It may indicate that the substitution of ligands affects the binding of complexes with BSA. A similar effect (more than one binding site) was observed in the interaction of cyclometallated iminophosphorane complexes and HSA as well [6]. Moreover this same effect was observed in a quantitative way (by isothermal calorimetry ITC) with other coordination palladium iminophosphorane complexes [35].…”
Section: Fluorescence Quenching Of Bsa By Complexes 1e8supporting
confidence: 69%
“…21 We have also reported on the cytotoxicity of coordination and organometallic Pt(II) and Pd(II) complexes with water-soluble iminophosphorane ligands. 22,23 Interestingly, we observed that some of these Pt and Pd compounds ( b – d ) were more cytotoxic than cisplatin to leukemia cell lines (both T-Jurkat and cisplatin-resistant Jurkat sh-Bak) by a mode of action different to that of cisplatin. 22,23 …”
Section: Introductionmentioning
confidence: 92%
“…5558 Organogold(III) complexes containing iminophosphorane (C,N-IM) ligands of the type PPh 3 =NPh displayed a high cytotoxicity in vitro against human ovarian cancer and leukemia cell lines (in some cases with IC 50 values in the nanomolar range) 55,56 while being less toxic to normal T-lymphocytes by a non-cisplatin mode of action (involving mitochondrial production of reactive oxygen species). 56 More recently, we have reported on the cytotoxicity of coordination and organometallic Pt(II) and Pd(II) complexes with water-soluble iminophosphorane ligands.…”
Section: Introductionmentioning
confidence: 99%